The far extracellular CUB domain of the adhesion GPCR ADGRG6/GPR126 is a key regulator of receptor signaling - Sumit J. Bandekar; Ethan E. Dintzner; Katherine Leon; Szymon P. Kordon; Tomasz Slezak; Kristina Cechova; Reza Vafabakhsh; Demet Araç (Proceedings of the National Academy of Sciences, 2025)
Adhesion G protein–coupled receptors (aGPCRs) transduce extracellular adhesion events into cytoplasmic signaling pathways. ADGRG6/GPR126 is an aGPCR critical for axon myelination, heart development, and ear development; ADGRG6 is also associated with developmental diseases and cancers. ADGRG6 has a large, alternatively spliced, five-domain extracellular region (ECR) that samples different conformations and is essential for receptor function in vivo. However, the mechanistic details of how the ECR regulates signaling are unclear. Herein, we studied the conformational dynamics of the conserved CUB domain which is located at the distal N terminus of the ADGRG6 ECR and is deleted in an alternatively spliced isoform (ΔCUB). We show that the ΔCUB isoform has decreased signaling and is insensitive to inclusion of an activating splice insertion (+ss). Molecular dynamics simulations suggest that the CUB domain is involved in interdomain contacts to maintain a compact ECR conformation. A cancer-associated CUB domain mutant, C94Y, drastically perturbs the ECR conformation and results in elevated signaling, whereas another CUB mutant located near a conserved Ca 2+ -binding site, Y96A, decreases signaling. Our results suggest an ECR-mediated mechanism for ADGRG6 regulation in which the CUB domain instructs conformational changes within the ECR to regulate receptor signaling.